2018
DOI: 10.1007/s00784-018-2497-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of nicotinamide N-methyltransferase in HSC-2 OSCC cell line: effect on apoptosis and cell proliferation

Abstract: The involvement of NNMT in cell growth and anti-apoptotic mechanisms seems to suggest that this enzyme could be a new therapeutic target to improve the survival of OSCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 31 publications
2
34
1
Order By: Relevance
“…Results obtained showed that Ki-67 levels did not undergo dysregulation upon induction of NNMT upregulation, thus suggesting that proliferative capacity of cancer cell is a complex phenotypical aspect regulated by the combined effects of different molecular determinants. 35 In conclusion, this report is the first to evaluate NNMT expression in odontogenic lesions and to demonstrate a differential expression between recurrent AMs and OKCs.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…Results obtained showed that Ki-67 levels did not undergo dysregulation upon induction of NNMT upregulation, thus suggesting that proliferative capacity of cancer cell is a complex phenotypical aspect regulated by the combined effects of different molecular determinants. 35 In conclusion, this report is the first to evaluate NNMT expression in odontogenic lesions and to demonstrate a differential expression between recurrent AMs and OKCs.…”
mentioning
confidence: 65%
“…Concerning cell proliferation, Ki‐67 expression was therefore investigated. Results obtained showed that Ki‐67 levels did not undergo dysregulation upon induction of NNMT upregulation, thus suggesting that proliferative capacity of cancer cell is a complex phenotypical aspect regulated by the combined effects of different molecular determinants …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…24 On the contrary, the induction of enzyme overexpression in HSC-2 oral cancer cells significantly enhanced in vitro cell proliferation. 25 These data demonstrated a pivotal role played by the enzyme in cancer cell metabolism and suggests that NNMT could represent an important molecular target for anticancer therapy.…”
Section: Introductionmentioning
confidence: 88%